Paeonol Protects Rat Heart by Improving Regional Blood Perfusion during No-Reflow - Ma, Lina; Chuang, Chia-Chen; Weng, Weiliang; Zhao, Le; Zheng, Yongqiu; Zhang, Jinyan; Zuo, Li (Frontiers in Physiology, 2016)
No-reflow phenomenon, defined as inadequate perfusion of myocardium without evident artery obstruction, occurs at a high incidence after coronary revascularization. The mechanisms underlying no-reflow is only partially understood. It is commonly caused by the swelling of endothelial cells, neutrophil accumulation, and vasoconstriction, which are all related to acute inflammation. Persistent no-reflow can lead to hospitalization and mortality. However, an effective preventive intervention has not yet been established. We have previously found that paeonol, an active extraction from the root of Paeonia suffruticosa, can benefit the heart function by inhibiting tissue damage after ischemia, reducing inflammation and inducing vasodilatation. For further a more focused investigation of the potential cardioprotective action of paeonol on no-reflow, healthy male Wistar rats were randomly divided into four groups: sham, ischemia-reperfusion (I/R) injury (left anterior descending coronary artery was ligated for 4h followed by reperfusion for 8 h), and I/R injury pretreated with paeonol at two different doses. Real-time myocardial contrast echocardiography was used to monitor regional blood perfusion and cardiac functions. Our data indicated that paeonol treatment significantly reduces myocardial infarct area and no-reflow area (n = 8; p < 0.05). Regional myocardial perfusion (A·β) and cardiac functions such as ejection fraction, stroke volume, and fractional shortening were elevated by paeonol (n = 8; p < 0.05). Paeonol also lowered the serum levels of lactate dehydrogenase, creatine kinase, cardiac troponin T and C-reactive protein, as indices of myocardial injury. Paeonol exerts beneficial effects on attenuating I/R-associated no-reflow injuries, and may be considered as a potential preventive treatment for cardiac diseases or post-coronary revascularization in which no-reflow often occurs.